MANEJO DE DOENÇAS FOLIARES, COMPLEXO GRÃO ARDIDO E IDENTIFICAÇÃO DA MICOFLORA EM GRÃOS DE MILHO - Vaz Júnior, Cláudio (2017)
Corn is one of the most important cereals currently cultivated, moreover, is of utmost importance for human and animal consumption, highlighting the role to be in the food chain and its agronomic value in tillage. Brazil is the third largest producer and second largest exporter of corn and the Paraná is the second largest national cereal producer, behind only in the state of Mato Grosso. Occupying the most diverse soil and climatic regions, corn has become more vulnerable to the occurrence of diseases, particularly those caused by fungi, such as leaf diseases and diseases of corn, which cause the rot grains that reduce productivity and cheapen the product. Today, much has been said about the use of fungicides to control disease in corn thus aimed to this work was to evaluate the efficiency of the combination of two fungicides with three numbers of applications in the control of foliar diseases and complex grain flamed corn, as well as to carry out the identification of mycoflora associated to the grains in two different commercial hybrids and two strains of maize breeding program UNICENTRO. The experiment was conducted in Guarapuava / PR, the experimental design was a factorial 4x7, which were evaluated four genotypes of corn against the seven chemical control combinations. The characteristics evaluated were severity of foliar diseases (leaf blotch, gray leaf spot), incidence of injuried grains, thousand grain weight, grain yield and the identification of mycoflora associated with damaged kernels and apparently healthy corn. The results demonstrated that it is feasible the use of chemical control for reducing the severity of disease, reducing the incidence of damaged kernels, and increase productivity and efficiency dependent on that genotype, fungicidal and number of applications. The main fungi found associated with corn rot grains were Fusarium spp., Stenocarpella spp. and Penicillium spp.